User Selective Encryption Method for Securing MANETs - Amal Ahmad; Shereen Ismail (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Security issue is getting important day by day. At present, there are a variety of methodologies to provide protection for data confidentiality. MANETs have lots of security challenges than traditional networks like infrastructureless and self-organizing requirements. As the MANETs are dynamic networks that’s make every transmission in such networks vulnerable to many attacks and improving security level becomes a main issue. This paper introduces a user selective encryption method by operating Data Encryption Standard (DES), Triple DES (3DES), Advanced Encryption Standard (AES) and the Diffie-Hellman Key Exchange (DHKE) protocol for key management in order to improve MANET security. Through the Network Simulator-2 (NS-2), the we investigate the performance of the proposed method in terms of data transfer time and network throughput for different data sizes and different sender-to-receiver number of hops. The results show the superiority of AES over other encryption algorithms. Furthermore, the effectiveness of our proposed method is verified through comparing our results with those obtained from previous studies.